Rejection of bronchus transplants in humanized mice is regulated by allogeneic CD4+CD25+ T cells - Knöfel, AK; Madrahimov, N; Salman, J; Büchler, G; Avsar, M; Sommer, W; Jonigk, D; Haverich, A; Warnecke, G (The Thoracic and cardiovascular surgeon, 2013)
Introduction: Bronchiolitis obliterans syndrome (BOS) limits long term survival after lung transplantation. CD4+CD25+ regulatory T cells are known to counteract acute rejection and may as well inhibit chronic rejection, i.e. BOS. We have developed a humanized mouse model in immune deficient NRG mice that are transplanted with allogeneic human small bronchus segments heterotopically. In this model, BOS-like pathology develops within 28 days. Here, we hypothesized regulatory T cells (Treg) would be important regulators of the BOS-like lesions in this humanized model. Methods: Small bronchus segments sampled from size reduced donor lungs during lung transplantation were transplanted under the skin of immune deficient NODrag-/-gammac-/- (NRG) mice. 5 × 10 6 human PBMC were injected per animal in 5 groups (n = 4 – 15). Group A received no PBMC, for group B cells and vessels were collected from two different donors, group C recipients received allogeneic PBMC depleted of CD4 + CD25 + T cells; group D recipients received allogeneic PBMC enriched of CD4 + CD25 + T cells. Alloinjury of the heterotopic bronchus grafts was assessed in histology on postoperative day 28. Results: In the control group A epithelial loss (p < 0.0001), cell infiltration and luminal obstruction (p < 0.0001) were absent and structural damage to the cartilage and the epithelium was low. In group B epithelial loss was pronounced and cell infiltration and histological changes were severe. In group C these changes were even more severe. In group D, cell infiltration was reduced and histological damage to the allografts was less severe, as was the epithelial loss. Conclusion: Heterotopic transplantation of a human bronchus graft and reconstitution with allogeneic human PBMC in NRG mice represents a valuable setting for transplant research. In vivo we could show that rejection of bronchus transplants is controlled by CD4 + CD25 + regulatory T cells. These results provide further evidence that BOS following lung transplantation may be subject to immune regulation. Thus, strategies enhancing regulatory T cells might be effective.